2007
DOI: 10.1063/1.2747185
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal spatial hole burning in terahertz quantum cascade lasers

Abstract: The propagation of a quasi-single-cycle terahertz pulse through an active terahertz quantum cascade laser is studied. The terahertz pulse is found to be diffracted on the optically induced longitudinal modulation of the refractive index of the laser active region. This modulation is a result of longitudinal spatial hole burning due to the formation of a standing wave in the laser cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Other THz studies on QCLs focused on gain dynamics below and above lasing threshold (Kuehn et al, 2008;Jukam et al, 2009), the charge carrier mobility and density (LloydHughes et al, 2009), observed spatial hole burning (Kroll, Darmo et al, 2007), spectral gain narrowing (Jukam et al, 2008), and identified the charge injection process from the injector layer into the upper laser state as being coherent, i.e., through resonant tunneling (Eickemeyer et al, 2002). …”
Section: Quantum Wellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other THz studies on QCLs focused on gain dynamics below and above lasing threshold (Kuehn et al, 2008;Jukam et al, 2009), the charge carrier mobility and density (LloydHughes et al, 2009), observed spatial hole burning (Kroll, Darmo et al, 2007), spectral gain narrowing (Jukam et al, 2008), and identified the charge injection process from the injector layer into the upper laser state as being coherent, i.e., through resonant tunneling (Eickemeyer et al, 2002). …”
Section: Quantum Wellsmentioning
confidence: 99%
“…Kroll, Darmo et al (2007) studied the polarization dynamics of AlGaAs/GaAs THz QCLs that lased at a frequency of 2.9 THz. The THz probe pulse was generated by a photoconductive antenna, coupled into the QCL waveguide and its transmission detected by EO sampling.…”
Section: Quantum Wellsmentioning
confidence: 99%
“…8,9 Recently, terahertz timedomain spectroscopy (TDS) has been shown to be a powerful technique to measure the gain spectra in terahertz QCLs. 10,11,12 Here, a broadband terahertz probe pulse is coupled into the QCL, and the electric field of the transmitted pulses is measured using electrooptic sampling. 13 In this letter terahertz TDS is used to investigate the line-width of the spectral gain as a function of current density.…”
mentioning
confidence: 99%
“…16 Another possible mechanism affecting the 3D spatial distribution of the guided modes is gain guiding induced by an inhomogeneous current distribution in the plane. 17 To investigate further the possibility of gain guiding we deliberately forced a nonuniform current distribution in the device with a central slit by electrically biasing only one of the top metal pads. The effect is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%